DEVELOPMENT AND VALIDATION OF BIOANALYTICAL METHOD FOR THE ESTIMATION OF DARUNAVIR AND CEFALEXIN IN HUMAN PLASMA (International Journal of Food and Nutritional Sciences, 2022)
Rapid and sensitive HPLC method has been developed for the determination of Darunavir and Cephalexin in human plasma. The mobile phase employed is Acetonitrile: Water in the ratio of 50:50 v/v. Validation results proved that the developed method performs well with selectivity, precision, accuracy, stability and linearity for the concentration range of2- 12μg/ml of Darunavir and from 5μg/ml to 30μg/ml of Cephalexin to be found in human plasma. Ritonavir and Voriconazole is used as an internal standard and it suitable for the determination of drug in human plasma at different therapeutic dose levels. The Mean Peak plasma concentration reported is 6.7mg/lit. It utilizes liquid liquid extraction with Dichloromethane as the sample preparation technique. The mean recovery of Darunavir is found to be 94.26% and in